The Cambridge world history of violence / Volume 4 1800 to the present / edited by Louise Edwards (University of New South Wales, Sydney), Nigel Penn (University of Cape Town), Jay Winter (Yale University) - Edwards, Louise; Penn, Nigel; Winter, Jay; Dwyer, Philip; Damousi, Joy (The Cambridge world history of violence, 2020)
This book explores one of the most intractable problems of human existence - our propensity to inflict violence. It provides readers with case studies of political, social, economic, religious, structural and interpersonal violence from across the entire globe since 1800. It also examines the changing representations of violence in diverse media and the cultural significance of its commemoration. Together, the chapters provide in-depth understanding of the ways that humans have perpetrated violence, justified its use, attempted to contain its spread and narrated the stories of its impacts. Readers also gain insight into the mechanisms by which the parameters about the acceptable limits to and locations of violence have dramatically altered over the course of a few decades. Leading experts from around the world have pooled their knowledge to provide concise, authoritative examinations of the complex phenomenon of human violence. Annotated bibliographies provide overviews of the shape of the research field.